Penerapan Strategi Active Learning Berbasis Teknologi Informasi pada Mata Pelajaran PAI di Pondok Pesantren Darurahmah Sepadan Aceh - Cibro, Iin Permata Puspita Sari; Tanjung, Ellisa Fitri (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to evaluate how information technology-based active learning strategies are implemented in Islamic Religious Education (PAI) subjects at the Darurahmah Sepadan Aceh Islamic Boarding School, using a qualitative approach. Descriptive methods are used to explore how information technology, especially visual and audio-visual media, is applied in the learning process and its impact on student engagement and understanding. Data was collected through in-depth interviews with teachers and the targets in this research were students, direct observation at the Darurahmah Islamic Boarding School in Sepadan Aceh, as well as analysis of related documents. Research findings show that the application of information technology-based active learning increases student engagement in a more interactive and interesting way. The use of visual and audio-visual media helps students understand Islamic Religious Education material better and relate it to real life contexts. Although this method brings many advantages, such as increasing student motivation and reducing feelings of laziness, this research provides valuable insights for the development of more innovative and effective learning strategies in the context of religious education.